Human haemato-endothelial precursors: cord blood CD34+ cells produce haemogenic endothelium. - Elvira Pelosi (Public Library of Science (PLoS), 2012)
Embryologic and genetic evidence suggest a common origin of haematopoietic and endothelial lineages. In the murine embryo, recent studies indicate the presence of haemogenic endothelium and of a common haemato-endothelial precursor, the haemangioblast. Conversely, so far, little evidence supports the presence of haemogenic endothelium and haemangioblasts in later stages of development. Our studies indicate that human cord blood haematopoietic progenitors (CD34+45+144-), triggered by murine hepatocyte conditioned medium, differentiate into adherent proliferating endothelial precursors (CD144+CD105+CD146+CD31+CD45-) capable of functioning as haemogenic endothelium. These cells, proven to give rise to functional vasculature in vivo, if further instructed by haematopoietic growth factors, first switch to transitional CD144+45+ cells and then to haematopoietic cells. These results highlight the plasticity of haemato-endhothelial precursors in human post-natal life. Furthermore, these studies may provide highly enriched populations of human post-fetal haemogenic endothelium, paving the way for innovative projects at a basic and possibly clinical level.